2015
DOI: 10.1002/ejic.201501154
|View full text |Cite
|
Sign up to set email alerts
|

Bad‐Metal‐Layered Sulfide Oxide CsV2S2O

Abstract: Through a solid-state reaction between stoichiometric amounts of a mixed cesium oxide Cs 2 O 1.3 , VS, S, and V 2 O 5 , a polycrystalline powder of CsV 2 S 2 O was obtained. Small single crystals could be grown in a CsCl melt by allowing Cs 2 SO 4 , V metal and S powders to react. The crystals have a plate-like morphology, consistent with the tetragonal crystal-structure [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Hence, to reach low formal oxidations states of transition metals, a combination of heavier chalcogenides with lighter ones can be the right strategy. Recently, the layered compound CsV2S2O was reported with V having the formally intermediate charge +2.5 [22]. However, metallic properties were observed, meaning that new systems have to be found for the study of the low oxidation states.…”
Section: Polar Coordinationsmentioning
confidence: 99%
“…Hence, to reach low formal oxidations states of transition metals, a combination of heavier chalcogenides with lighter ones can be the right strategy. Recently, the layered compound CsV2S2O was reported with V having the formally intermediate charge +2.5 [22]. However, metallic properties were observed, meaning that new systems have to be found for the study of the low oxidation states.…”
Section: Polar Coordinationsmentioning
confidence: 99%
“…For instance, Ba 2 Ti 2 Fe 2 As 4 O is an intergrowth of BaTi 2 As 2 O and BaFe 2 As 2 where T DW of 120 K is observed, which is lower than that in BaTi 2 As 2 O due to the interlayer charge transfer [60]. Both CsV 2 S 2 O and Cs 1-x Ti 2 Te 2 O have the same structure as BaTi 2 Pn 2 O, but they do not show any DW instability, while they show bad-metal and metallic conduction, respectively [61,62]. Though no superconductor has been found in ATi 2 Pn 2 O-related compounds yet, the discovery of superconductivity in titanium pnictide oxides might give rise to new classes of superconductors, just as cuprates and Fe-based superconductors have given rise.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, various ATi2Pn2O-related compounds, such as pnictide oxides and chalcogenide oxides, have been found [60][61][62][63][64]. For instance, Ba2Ti2Fe2As4O is an intergrowth of BaTi2As2O and BaFe2As2 where TDW of 120 K is observed, which is lower than that in BaTi2As2O due to the interlayer charge transfer [60].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, this kind of transition was not seen in CsV 2 S 2 O. [9] However, the V 2 Se 2 O sample exhibits a very distinct electric transport property, as shown in Figure 3(a) and (d). Firstly, the resistivity of V 2 Se 2 O is much larger than that of CsV 2 Se 2 O and CsV 2 Se 1.5 O. Secondly, with decreasing temperature, it increases monotonously without any anomaly.…”
Section: Methodsmentioning
confidence: 87%
“…suggested that the Ni-based compounds (LaO) 2 Ni 2 Se 2 O containing the [Ni 2 M 2 O] 2− (M =chalcogen) layers with the similar structure mentioned above may be potential high-temperature superconductors upon doping or applying pressure [8]. Furthermore, another system CsV 2 S 2 O [9] with the isostructure * Electronic address: zhuxiyu@nju.edu.cn,hhwen@nju.edu.cn but different-valent [V 2 S 2 O] − layer was reported to be a paramagnetic bad-metal. Therefore it is very interesting to explore and investigate the 3d (probably also 4d) transition-metal systems with the similar [T 2 Q 2 O] structural units.…”
Section: Introductionmentioning
confidence: 99%